2022
DOI: 10.34012/jkpi.v2i2.1196
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Kepemilikan Jamban Sehat Keluarga Di Desa Busung Kecamatan Teupah Tengah Kabupaten Simeulue

Abstract: Abstract             The latrine is a place that is used to remove feces or human waste. Making latrines is a human effort to maintain health by making the environment a healthy place. Based on the results of an initial survey of 10 households at Desa Busung, Teupah Tengah Sub District, Simeuleu District, 7 households had latrines that did not meet the requirements of healthy latrines and 3 households had latrines that met the requirements of healthy latrine. of this study was to determine the factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…This is because the higher public awareness will create a healthy environment. This is supported by the results of Endang's research in 2020, which found no relationship between the role of officers and ownership of healthy latrines [13].…”
Section: The Relationship Between Health Workers and Healthy Latrine ...mentioning
confidence: 81%
See 1 more Smart Citation
“…This is because the higher public awareness will create a healthy environment. This is supported by the results of Endang's research in 2020, which found no relationship between the role of officers and ownership of healthy latrines [13].…”
Section: The Relationship Between Health Workers and Healthy Latrine ...mentioning
confidence: 81%
“…There are also those who say that the health workers never come let alone provide education. Respondents said that the promotion regarding the use and utilization of latrines, both those that already existed or those who did not yet have a latrines, was not carried out optimally by health workers, the invitation to make use of latrines was only felt by a few respondents [13].…”
Section: The Relationship Between Health Workers and Healthy Latrine ...mentioning
confidence: 99%
“…e. Upaya pemeliharaan Jamban sehat 13 . Salah satu upaya dalam meningkatkan standar kesehatan masyarakat dalam penggunaan jamban sangatlah penting dalam peningkatan sarana sanitasi dasar 14 .…”
Section: Gambar 1 and 2: Kegaiatan Penyuluhanunclassified
“…Salah satu masalah sanitasi di rumah tangga yaitu masalah pada akses pembuangan tinja. Penggunaan jamban sehat sangat penting sebagai sarana sanitasi dasar serta upaya dalam meningkatkan derajat kesehatan masyarakat (Maryanti et al, 2020;AW et al, 2020).…”
Section: Pendahuluanunclassified